What counts as theory, today? A post-philosophical framework for socio-legal empirical research - Valverde, Mariana (Revista de Estudos Empíricos em Direito, 2016)
While legal researchers’ skepticism about much of what is on offer under the name of theory is well grounded, there are nevertheless theoretical resources that can very much benefit empirical researchers. Neither legal philosophy nor grand European sociology of law are particularly helpful, and in many respects these traditions constitute obstacles to concrete analyses of legal processes. But fortunately, today, there are other sources of theoretical and methodological inspiration. Here I present a small part of my own recent contribution to the project of revising ‘theory’ in a way that is more helpful to legal and empirical researchers than traditional philosophy and sociology.